2020
DOI: 10.1038/s41598-020-63025-4
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional HIV-1 specific response by CD8+ T lymphocytes expressing high levels of CD300a

Abstract: CD300a receptor is found on different CD8+ T cell subsets and its expression has been associated to a more cytotoxic molecular signature. CD300a has an important role in some viral infections and its expression levels are known to be modulated by human immunodeficiency virus (HIV)−1 infection on several cell types. The main objective of this work was to investigate CD300a expression and its regulation during HIV-1 specific CD8+ T cell responses. CD300a receptor expression was analysed by multiparametric flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(106 reference statements)
1
2
0
Order By: Relevance
“…In other words, neonatal T cells are less polyfunctional, which could subsequently lead to less potent T cell responses (96). In a recent study on HIV-1 responses by CD8 + T cells, the results showed that HIV-1 specific adult CD8 + T cells with high frequencies of CD300a were more polyfunctional (111). These observations are in line with the difference in CD300a expression levels between adults and neonates, as described in the previous paragraph.…”
Section: Functional Differencessupporting
confidence: 77%
“…In other words, neonatal T cells are less polyfunctional, which could subsequently lead to less potent T cell responses (96). In a recent study on HIV-1 responses by CD8 + T cells, the results showed that HIV-1 specific adult CD8 + T cells with high frequencies of CD300a were more polyfunctional (111). These observations are in line with the difference in CD300a expression levels between adults and neonates, as described in the previous paragraph.…”
Section: Functional Differencessupporting
confidence: 77%
“…Gate defining the positive production of cytokines and cytotoxic molecules were combined by the boolean gating strategy as indicated in the FlowJo software. The polyfunctional profile was defined as the capacity of CD8 + T-cells to produce multiple markers simultaneously [ 23 , 24 ]. The percentage of cells exhibiting from one to six functions was analyzed as previously described using the SPICE v5.35 software [ 22 , 25 ].…”
Section: T-cell Countsmentioning
confidence: 99%
“…The relevance of the CD300a molecule in several pathological conditions has been highlighted by multiple studies [ 3 , 4 , 5 , 6 , 7 ]. Among others, CD300a has been related to bacterial, parasitic, and viral infections [ 4 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. For instance, after cecal ligation and puncture peritonitis in mice, the absence of CD300a induced a more effective bacterial clearance and prolonged mice survival by increasing mast cell inflammatory response and neutrophil recruitment [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, after cecal ligation and puncture peritonitis in mice, the absence of CD300a induced a more effective bacterial clearance and prolonged mice survival by increasing mast cell inflammatory response and neutrophil recruitment [ 16 , 17 ]. CD300a is broadly expressed on myeloid and lymphoid cells, and its expression is known to be differentially regulated depending on the cell type [ 11 , 12 , 13 , 14 , 15 , 18 , 19 , 20 , 21 , 22 , 23 ]. Regarding B cells, besides some aspects of the expression and function of CD300a on several human B cell subsets, its relevance in B cell leukemogenesis, and its potential relevance in viral infections [ 23 , 24 , 24 , 25 , 26 ], its role is not completely known.…”
Section: Introductionmentioning
confidence: 99%